Shareholder litigation, shareholder–creditor conflict, and the cost of bank loans - Chu, Yongqiang (Journal of Corporate Finance, 2017)
I study how shareholder litigation affects the cost of bank loans via its impact on the distribution of bankruptcy estate and the conflict of interests between shareholders and creditors. Using a natural experiment based on a ruling by the Ninth Circuit Court of Appeals, I find that increasing the difficulty of class action suits decreases loan spreads. The effect is stronger for firms with higher institutional ownership, which is consistent with the argument that class actions suits help shareholders extract wealth from creditors when the firm is in bankruptcy. Further analysis shows that the effect is weaker for firms with stronger creditor protection in bankruptcy.